Effect of aqueous extract of native potato Solanum tuberosum "puca simi" on enzymes of phase II detoxification - Ramírez, Emilio (2014)
The objective of this study was to evaluate the effect of aqueous extract of native potato Solanum tuberosum "puca simi " on detoxification enzymes of phase II. Were used 28 male rats Rattus norvegicus strain of 200 to 250 g, that were grouped into four groups of seven each, receiving by orogastric way: Group I control, saline; Group II, phenylhydrazine 60 mg/kg; Group III, potato extract 665 mg/kg; Group IV, potato extract and phenylhydrazine. Were determined levels of total protein, total bilirubin, malondialdehyde (MDA), hematocrit; the activities of glutathione S-transferase (GST) and UDP-glucuronyltransferase. The phytochemical study identified polyphenols, flavonoids and saponins. A significant decrease in hematocrit levels, total bilirubin, and total protein in groups III and IV regarding the control and group II was found, also a significant (p<0,05) malondialdehyde in group III (1,53 ŋg/g tissue) and IV (1,56 ŋg/g tissue) compared to group II (2,03 ŋg/g tissue). The specific activity of UDP-glucuronyl transferase increased significantly (p<0,01) in group IV compared to the control and other groups, and the specific and total activity of glutathione S-transferase exhibits no significant difference in the four groups. It is concluded that the aqueous extract of native potato "pucca simi" contains secondary metabolites that protect lipid peroxidation and significantly increases the activity of the UDP-glucuronosyltransferase.